Time delay performance analysis of sensor allocation strategies on a WSN - BAYANI, MAJID (2011)
In many of query-based WSN applications, response time factor is an essential issue. Overall performance under different sensor placements depends on the pattern of queries requested from the network, which in turn might depend on the physical segmentation of the field. This paper explores three predefined configurations in order to compare the time delay performance. The experiments showed that the Uniform distribution of the nodes was the strategy that obtains the fastest response time, and as expected, Random is the one with the slowest.